Społeczne usytuowanie pojęcia dystynktywności wśród określeń synonimicznych - Lapis, Włodzimierz (Investigationes Linguisticae, 2008)
According to Tokarski 1980, distinctive means – ‘distinguishing, differing’. So much for a definition. However, this work will explore how this notion can be understood through analysis of specific texts in which it occurs. We will also address other questions, such as: what kinds of distinctive features there are, and how distinctiveness ranks among other concepts, including those which are regarded as its synonyms.